2009
DOI: 10.1068/a40260
|View full text |Cite
|
Sign up to set email alerts
|

A Particular Place? Laos and its Incorporation into the Development Mainstream

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 28 publications
1
17
0
1
Order By: Relevance
“…The attraction of NTFPs lies in the fact that they are often regarded as free goods (Ambrose-Oji 2003). Forests are repositories of village food and wealth and buffers during times of crisis (Rigg 2009), and as such NTFPs may be harvested for both subsistence and commercial purposes (Ambrose-Oji 2003; Ndangalasi et al 2007). In some areas (such as rural Laos) they may contribute as much as 46% to the household economy (NBSAP 2004).…”
Section: Non-timber Forest Products (Ntfps)mentioning
confidence: 99%
“…The attraction of NTFPs lies in the fact that they are often regarded as free goods (Ambrose-Oji 2003). Forests are repositories of village food and wealth and buffers during times of crisis (Rigg 2009), and as such NTFPs may be harvested for both subsistence and commercial purposes (Ambrose-Oji 2003; Ndangalasi et al 2007). In some areas (such as rural Laos) they may contribute as much as 46% to the household economy (NBSAP 2004).…”
Section: Non-timber Forest Products (Ntfps)mentioning
confidence: 99%
“…The high nutritional value, the easy access, the lack of cares and the good organoleptic quality of WEFT species have led to their overexploitation even in natural forests which constitute the reservoir of WEFT species (Rigg et al, 2009). Within the same context, FAO (2010) reported that African forests' coverage decreases at an alarming rate due to human pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Lao farmers, particularly in the uplands, have always been to some extent ‘on the move’, whether to evade conflict or state intrusion, maintain access to resources, engage in exchange or as a result of policies towards managing rural areas (World Bank ; Walker ; Scott ; Évrard and Baird ), and present‐day mobility is arguably an extension of these movements. However, it is inescapable that today's rural Lao population is on the move in different ways, in larger numbers and for different reasons—especially relating to rural development policies and the impacts of market integration—than in past times (Évrard and Goudineau ; Rigg , ; Rungmanee ; Bouté ). So, while we can say that Lao peasants have never been ‘immobile’, we should not regard the present as simply a smooth transition from the past.…”
Section: Introduction: Lao Peasants In a Changing Worldmentioning
confidence: 99%